Determination of contamination severity on the surface of high voltage insulators near coastal area - Hussein Ahmad, 1953-; Md. Abdus Salam, 1965-; Zolkafle Buntat; Tarmidi Tamsir; Ahmad S. Ahmad; International Power Engineering Conference (1999 : Singapore)
15